(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the educational programs created by the teachers of "Engineering and computer graphics" at the department of "General Engineering Sciences" of the Institute of Engineering Economics, Karshi, they will create schemes based on the direction and learn the conditional graphic designations used in these schemes. Great importance is attached to learning. In particular, efforts are being made to create methodological support for the students of the 60712500 - Vehicle engineering (automotive transport) department, which will help students to develop their knowledge and skills in the implementation of specialty schemes.